Meningkatkan Semangat Digital Enterpreneurship Dengan Literasi Digital di SMKN 2 Manado - Purnomo, Kharies Dwi Manosoh; Giroth, Lady Grace Jane; Wangania, Diana; Rumengan, Hendry; Tumiwa, Only Yonathan; Taroreh, Yoberts Kenzhu (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
At In this modern era, the development of Digital Technology has become an essential need in various community activities, resulting in almost every place you visit visited has integrated the technology. With the widespread digitalization, the ability to use Digital Technology effectively and wisely becomes very important. wisely becomes very important. Digital Literacy plays a crucial role in this, especially in the educational environment. This article discusses how digital literacy can improve people's understanding and skills in using technology, focusing on its implementation at SMK Negeri 2. using technology, focusing on its implementation at SMK Negeri 2 Manado. The purpose of this digital literacy is to ensure that students can utilize technology in an effective and responsible way, preparing them to face the demands of an ever-evolving digital world. evolving digital world.